Multi-degree cyclic flow shop robotic cell scheduling problem: Ant colony optimization. (September 2016) - Elmi, Atabak; Topaloglu, Seyda
Abstract: This paper deals with the multi-degree cyclic robotic flow shop cell scheduling problem with multiple robots. All the parts are processed successively through the machines with standard processing times while single gripper robots perform the transportation operations of parts between the machines. Due to the special characteristics of the considered problem, a metaheuristic algorithm based on ant colony optimization has been proposed. The proposed algorithm simultaneously determines the optimal degree of the cyclic schedule, the robot assignments for the transportation operations, and the optimal sequence of robots' moves, which in return maximize the throughput rate. The efficiency of the proposed metaheuristic algorithm is examined by a computational study on a set of randomly generated problem instances. Highlights: This research studies the k -degree cyclic robotic flow shop cell scheduling problem. Multiple single gripper robots are considered to perform transportation operations. An ACO based algorithm is proposed to minimize the cycle time for per produced part. The characteristics of the considered problem are stated by an instance problem. The proposed algorithm finds the appropriate cycle degree of the considered problem.